Isolation and diagnosis of bacteria causing gingivitis in patients with type 2 diabetes - Haifa Mohammed Almabrouk; Tahani Mohammed Helmy; Al-Aqla Ahmed Al-Hamoudi (Surman Journal of Science and Technology, 2025)
The aim of this research is Isolating the bacterial species that cause mouth infections from a sample of patients with type 2 diabetes and comparing them to the control group, and diagnosing the type of bacteria causing the contamination inside the mouth. The cases were divided into two groups. The first group included 30 cases with type 2 diabetes and suffering from gingivitis, while the second group included 30 cases without diabetes (control sample) inside the dental clinic at Sabratha Teaching Hospital, where swabs were taken with a Swab for both groups for a period of time. Between 18/4/2023 and 22/8/2023, the samples were then transferred to the laboratory for analysis and testing. Volunteers in the age group 30-70 with type II Diabetes and controls that were healthy individuals without diabetes, male and female, denture wearer or non- denture wearer, with or without oral lesion were included in the study. Those volunteers with steroid or antibiotic use in the last 4 weeks of study were excluded. The highest age group in Group A was > 60 years, and the percentage reached 43.3%. As for the second group, the highest percentage was for the age group 50-60 years, and the percentage reached 36.7%. The highest percentage of isolated samples in group A was Streptococcus mutans bacteria, which reached 33.3%, followed by Streptococcus anginosus, 20.4%. The highest percentage of isolated samples in group B (control sample) was Proteusus merapilis bacteria, which reached 47%, followed by Pseudomonas aeruginosa bacteria, which reached 35.4%.